Ambiguity and the Uncanny in Henry James’s "The Turn of the Screw" and Its Polish Translations (Między Oryginałem a Przekładem, 2017)
Henry James’s The Turn of the Screw poses an interpretative challenge to its researchers, readers, and translators. The unique character of the novelette, which is surrounded by the aura of the uncanny, is closely related to the ambiguous narrative and linguistic devices used by the author. Major interpretations of the text followed Gothic, Freudian, and metanarrative approaches. The paper sets out to investigate the extent to which the translations proposed by Witold Pospieszała and Jacek Dehnel adhere to any these approaches and whether and how they try to deal with the ambiguities that make James’s masterpiece so uncanny.